Cooling Working Rolls of the Finishing Section of Wide-Strip Hot Rolling Mills - Peter Horbaj; Jozef Víglasky; Dusan Mikolaj (Communications - Scientific letters of the University of Zilina, 2006)
The contribution deals with heat nucleation in rolling on the hot wide strip mill as well as into following transfer to the rolls without friction heat being involved. This work has resulted in the computer program owned by author. It represents the most accessible computer technique and the dependence of the accepted heat amount on the revolutions and angle of bite, as well as the dependence on the temperature of the roll surface which may participate in the initiation and widening of the surface friction coefficient and roll stand sequence.